2014
DOI: 10.1007/s00114-013-1140-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the compositional differences between humic fractions isolated by the IHSS and exhaustive extraction procedures

Abstract: Humic substances (HSs), consisting, on the basis of solubilities in aqueous acid and basic media, of humic acids (HAs), fulvic acids (FAs), and humin (Hu), are the major components of soil organic matter (SOM). Most studies of soil/natural organic matter (SOM/NOM) have been carried out on extracts of soils in dilute sodium hydroxide solutions, the solvent used to extract the Standards of the International Humic Substances Society (IHSS). However, Hu, the major component in the classical definition of HSs, is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…The E 4 /E 6 ratio was ascertained by measuring approximately 2.0 mg of humin in 10 mL of a NaHCO 3 0.05 mol L À1 solution and later reading the absorbance at 465 and 665 nm on a DR 3900 spectrometer [13,22].…”
Section: Uv-vis Spectroscopy: Determination Of the E 4 /E 6 Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…The E 4 /E 6 ratio was ascertained by measuring approximately 2.0 mg of humin in 10 mL of a NaHCO 3 0.05 mol L À1 solution and later reading the absorbance at 465 and 665 nm on a DR 3900 spectrometer [13,22].…”
Section: Uv-vis Spectroscopy: Determination Of the E 4 /E 6 Ratiomentioning
confidence: 99%
“…Among the naturally occurring substances that have this characteristic and that are globally distributed in aquatic and land ecosystems, humic substances (HS) stand out [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low E 4 /E 6 ratios are considered to be indicative of the relatively higher degree of aromatization while high ratios indicate more aliphatic structures in the organic fractions (Chang et al, 2014).…”
Section: Uv -Vis Spectroscopymentioning
confidence: 99%
“…Litter decomposition increased the proportions of carboxyl C, alkyl C and aromatic C, and decreased that of O-alkyl C in forest (Zech et al 1997). Balanced fertilizer increased alkyl-C/O-alkyl-C ratio and decreased aromaticity in maize-wheat rotation system (Xu et al 2017a), and further improved the aliphatic nature of humin (Chang et al 2014, Xu et al 2017b. All these suggested that soil management would change the structural composition of SOC.SOC derives mainly from plant residues and thus land-cover change will lead to variation in the molecular nature of SOC (Wickings et al 2012) due to quality and composition of various plant residues.…”
mentioning
confidence: 99%